Correlations between changes in intestinal microbiota composition and performance parameters in broiler chickens. Issue 3 (30th September 2014) - Rubio, L. A.; Peinado, M. J.; Ruiz, R.; Suárez‐Pereira, E.; Ortiz Mellet, C.; García Fernández, J. M.
Summary: Growing male Cobb broiler chickens were fed on diets supplemented with additives reported as able to influence intestinal microbiota composition. The diets used were a balanced commercial diet (no additive), inulin (20 g/kg), fructose caramel (FC, 20 g/kg) and the garlic derivative PTS‐O (propyl propane thiosulfonate, 45 and 90 mg/kg diet). The composition of the intestinal microbiota was analysed by qPCR at different points of the intestinal tract, and a number of nutritional parameters were also determined. The relative amounts of bacteroides (bacteroides/total bacteria) in the ileal contents correlated (p < 0.05) positively with faecal NDF, ADF, hemicellulose and cellulose digestibility. The relative amounts of Escherichia–Shigella ( Escherichia–Shigella /total bacteria) in the crop contents correlated (p = 0.05) negatively with weight gain of broilers. Faecal N digestibility correlated (p < 0.05) negatively with total bacteria in the ileal contents of chickens. The relative amounts of Escherichia–Shigella ( Escherichia–Shigella /total bacteria) in the caecal contents correlated (p = 0.05) negatively with faecal fat digestibility of broilers. Total bacteria in ileal or caecal contents of growing chickens correlated (p < 0.05) negatively with ileal N digestibility. The results here reported suggest that positive or negative correlations can be found between performance parameters and changes in intestinal microbiota composition of growing broiler chickens.